Efektifitas Ketentuan Bebas Visa Kunjungan dalam Penyalahgunaan Izin Tinggal Warga Negara Asing - Ria Regger Effendi (Universitas Batanghari Jambi, 2023)
Indonesia is a country that has diverse natural resources with a uniqueness that is an attraction for local and foreign tourists. The era of globalization in all fields includes industry, investment, trade, services, transportation, telecommunications, tourism, finance. So to create an expansion of job opportunities for Indonesian workers and increase the number of tourist visits and expand in all other fields, the Government issued Presidential Regulation of the Republic of Indonesia Number 21 of 2016 concerning Free Visit Visa. The problem that will arise from the visit visa-free provisions is how effective is the supervision of visit visa-free permits based on Law Number 6 of 2011 and what is the impact of visit visa-free permits on the abuse of residence permits for foreign citizens. The research method used is normative juridical which only studies from the Presidential Regulation of the Republic of Indonesia Number 21 of 2016 and Law Number 6 of 2011, the data collection technique used is secondary data in the form of data obtained based on literature studies